Convergent Associative Motor Cortical Plasticity Induced by Conditional Somatosensory and Motor Reaction Afferents - Huang, Yi; Chen, Jui-Cheng; Tsai, Chon-Haw; Lu, Ming-Kuei (Frontiers in Human Neuroscience, 2020)
Objective: Associative motor cortical plasticity can be non-invasively induced by paired median nerve electric stimulation and transcranial magnetic stimulation (TMS) of the primary motor cortex (M1). This study investigates whether a simultaneous motor reaction of the other hand advances the associative plasticity in M1. Methods: Twenty-four right-handed subjects received conventional paired associative stimulation (PAS) and PAS with simultaneous motor reaction (PASmr) with at least a 1-week interval. The PASmr protocol additionally included left abductor pollicis brevis muscle movement responding to a digital sound. The motor reaction time was individually measured. The M1 excitability was examined by the motor evoked potential (MEP), short-interval intracortical inhibition (SICI), and intracortical facilitation (ICF) before and after the PAS protocols. Results: The conventional PAS protocol significantly facilitated MEP and suppressed SICI. A negative correlation between the reaction time and the MEP change, and a positive correlation between the reaction time and the ICF change were found in the PASmr protocol. By subgrouping analysis, we further found significant facilitation of MEP and a reduction of ICF in the subjects with fast reaction times but not in those with slow reaction times. Conclusion: Synchronized motor reaction ipsilateral to the stimulated M1 induces associative M1 motor plasticity through the spike-timing dependent principle. MEP and ICF change could represent this kind of plasticity. The current findings provide a novel insight into designing rehabilitation programs concerning motor function.